A nano-modified lubricating masterbatch and its preparation method and application

Through the use of nano -modified smooth mother grains in aluminum -plastic film, the existing aluminum -plastic film has insufficient punching performance, realizing the stable dispersing and low friction coefficients of smoothing agents, improving the depth performance and production efficiency of production and production efficiency Essence

CN116144108BActive Publication Date: 2025-01-28杭州福斯特功能膜材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310097815.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-10
Publication Date
2025-01-28
Estimated Expiration
2043-02-10

AI Technical Summary

Technical Problem

The existing aluminum-plastic film has insufficient depth performance, fast migration speed of slip agent and poor dispersion, resulting in high friction coefficient, astringent film, and easy to break in the depth process.

Method used

Using nano -modified smooth mother particles, including modified nanoparticles, migrant smoothing agents, polypropylene resin carriers, and antioxidants. Adding ability to a smooth agent.

Benefits of technology

Effectively reduce the migration speed of the sliding agent, avoid a large amount of accumulation on the surface of the aluminum -plastic film, maintain a low friction coefficient, improve the depth performance, and prevent damage to the depth process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004072233550000091
    Figure BDA0004072233550000091
  • Figure BDA0004072233550000101
    Figure BDA0004072233550000101
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer materials, and specifically relates to a nano-modified lubricant masterbatch and a preparation method and application thereof. The migratory lubricant of the present invention has a slow migration speed, and a large amount of lubricants will not migrate outward to the surface of the aluminum-plastic film to accumulate in a short time, which effectively avoids the contamination of the material. Compared with the non-migratory lubricant, it has good compatibility with the polyolefin resin matrix and is easier to disperse. In the preparation process of the polyolefin film, a good lubricant effect is achieved without affecting the subsequent processing performance, and the aluminum-plastic film is effectively prevented from being damaged during the deep punching process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a nano-modified lubricating masterbatch and a preparation method and application thereof. Background Art

[0002] With the booming development of power electronics industries such as new energy vehicles, e-cigarettes and digital 3C, the demand for batteries, which are core components, is also increasing. As a soft-pack lithium battery packaging material, aluminum-plastic film has good packaging, temperature resistance, oxygen barrier, moisture resistance, puncture resistance and corrosion resistance. In recent years, with people's increasing demand for battery capacity and rate, batteries are also developing in the direction of larger sizes, so the requirements for the deep punching performance of aluminum-plastic film are also getting higher and higher.

[0003] In order to improve the deep-drawing performance of aluminum-plastic film, the most commonly used method is to improve the compensation performance of the material during deep-drawing by reducing the friction coefficient of the film surface. Using inner and outer film materials with lower friction coefficients or applying lubricants on the surface of aluminum-plastic film are existing effective means. Common lubricants are divided into two types: migratory and non-migratory. Migratory lubricants are mainly organic waxes such as erucic acid amide and oleic acid amide, which can quickly migrate to the surface of the material to achieve slippage. However, as the storage time of the aluminum-plastic film increases, the lubricant migrates to the adhesive layer, causing the adhesion between the inner (outer) layer and the metal foil layer to deteriorate, causing the friction coefficient of the film material to increase, thereby reducing the deep-drawing performance. In addition, affected by temperature, the lubricant will precipitate in large quantities in a short time, accumulate on the film surface, and then transfer to the surface of the deep-drawing mold. In order to ensure the deep-drawing performance, the mold must be cleaned regularly, which affects production efficiency. Non-migratory lubricants and anti-adhesive agents such as organic siloxanes (silicones) have high relative molecular weights, and their relative molecular weights are 50 to 200 times that of primary amide lubricants. Since the relative molecular mass of this type of lubricant and anti-sticking agent is large and difficult to diffuse in the polymer matrix, the reduction of the friction coefficient of this type of lubricant and anti-sticking agent is achieved by the lubricant and anti-sticking agent reaching the resin surface during the polymer extrusion process, and no adjustment period is required.

[0004] In the technical solution of patent CN109705443A, a silicone opening lubricant masterbatch composition for plastic film is disclosed, which uses hollow glass microspheres as the opening component and selects silicone powder as the lubricating component to achieve good opening performance, and has the advantage of no precipitation while significantly reducing the friction coefficient. However, silicone powder is a high molecular weight polysiloxane, and mixing it into the film will affect the transparency of the film, and the dispersibility is not good.

[0005] In the technical solution of patent CN110041817A, silicon dioxide particles, amino-ether modified silicone resin and isocyanate are used as additives to form a smooth coating on the surface of the film. This can reduce the friction coefficient of the aluminum-plastic film surface and improve the deep-drawing performance of the aluminum-plastic film. However, it adopts a two-component structure, the temperature requirement of the oven is high, and the economic cost is also higher. At the same time, although the isocyanate curing agent used in the coating smooth liquid is unblocked at high temperature, it will react slowly at room temperature, so its smooth coating liquid has a certain timeliness. Summary of the invention

[0006] The present invention aims to overcome the defects in the prior art that the lubricant has a fast migration speed and poor dispersibility in the film, resulting in a high friction coefficient on the surface of the aluminum-plastic film, the film becoming astringent, and easy damage during the punching process. A nano-modified lubricant masterbatch and a preparation method thereof are provided, and the masterbatch is used in the preparation of polyolefin films and aluminum-plastic films.

[0007] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions:

[0008] A nano-modified lubricating masterbatch, comprising the following components:

[0009] Modified nanoparticles, migratory lubricant, polypropylene resin carrier and antioxidant;

[0010] The outer surface of the modified nanoparticles is chemically grafted with a silane coupling agent.

[0011] During the production of polyolefin films, vacuum is easily formed between the film surfaces, and the molecular chains on the two layers are entangled and adhered, which makes it difficult to separate and affects further production and application. Therefore, it is usually necessary to add an opening agent and a lubricant during the processing. The opening agent is generally a small inorganic particle such as talcum powder, silicon dioxide, etc., which can make the surface of the film micro-roughened. After the film is made, the small inorganic particles partially extend out of the film surface to form a protrusion, thereby avoiding the formation of a vacuum between the films after the film is closed. The compatibility of amide lubricants and polymers is limited. When mixed in the polymer, it will gradually migrate from the inside of the film to the surface of the film to form a lubricating layer, thereby effectively isolating the two adjacent layers of film, achieving a smooth effect, and also reducing the friction coefficient of the film. In the traditional polyolefin film production process, a single-component migratory lubricant is directly added. The migratory lubricant is easy to precipitate quickly, causing it to accumulate on the surface of the aluminum-plastic film in large quantities, causing pollution. Adding a high-molecular-weight non-migratory lubricant will affect the transparency and dispersibility of the film.

[0012] The inventor found after repeated experiments that nanoparticles, mobile lubricants, polypropylene resin carriers and processing aids are co-extruded and added to polypropylene plastic film as a lubricant masterbatch, and the nanoparticle components in the lubricant masterbatch are distributed inside the material. Nanoparticles are easily connected and agglomerated with each other, and further attracted to each other due to hydrogen bonding after agglomeration. The surface of the nanoparticles contains a large number of hydroxyls, which are difficult to be evenly dispersed in the resin, causing the nanoparticles to lose the adsorption effect on the mobile lubricant. It is then difficult to slow down the speed of the mobile lubricant to migrate outwards, and it is also difficult to avoid its rapid accumulation on the surface of the aluminum-plastic film. Therefore, the inventor modified the traditional nanoparticles by a silane coupling agent. Silane coupling agents are added to the lubricant masterbatch, which can react with the hydroxyl groups of the nanoparticles and have excellent compatibility with the resin at the other end, effectively improving the dispersibility of the nanoparticles. Further improve the adsorption effect of the nanoparticles on the mobile lubricant, effectively reduce the speed of the mobile lubricant to migrate outwards, thereby avoiding its large-scale accumulation on the surface of the aluminum-plastic film, causing pollution.

[0013] Preferably, a nano-modified lubricant masterbatch comprises the following substances in parts by weight:

[0014] 70-90 parts of polypropylene resin carrier, 5-15 parts of modified nanoparticles, 5-15 parts of migratory lubricant and 1-5 parts of antioxidant.

[0015] As a further preferred embodiment, a nano-modified lubricant masterbatch comprises the following substances in parts by weight:

[0016] 75-80 parts of polypropylene resin carrier, 8-10 parts of modified nanoparticles, 10-12 parts of migratory lubricant and 1-3 parts of antioxidant.

[0017] The lubricating masterbatch made of 75-80 parts of polypropylene resin carrier is selected and added to the polyolefin film for better dispersion effect. When the added polypropylene resin carrier is less than 70 parts, the other components in the lubricating masterbatch are high and the dispersibility is poor; when the added polypropylene resin carrier is more than 90 parts, the proportion of lubricating components is low and the lubricating performance is poor. When the added modified nanoparticles are less than 5 parts, the ability to adsorb the migratory lubricant is weakened; when the added modified nanoparticles are more than 15 parts, they are easy to agglomerate in the lubricating masterbatch, the dispersibility is poor, and it is difficult to limit the migration of the lubricant. When the added migratory lubricant is less than 5 parts, the lubricating performance is not enough; when the added migratory lubricant is more than 15 parts, it is easier to precipitate. When the added antioxidant is less than 1 part, it is difficult to play an antioxidant role; when the added antioxidant is more than 5 parts, it is easy to affect the overall dispersion and other properties of the material such as mechanics.

[0018] Preferably, the migratory lubricant is a combination of one or more of stearic acid amide, N,N-ethylenebisstearic acid, erucic acid amide, oleic acid amide, and stearyl n-butyl ester.

[0019] As further preferred, the migratory lubricant is a combination of one or more of erucamide, stearamide and oleamide.

[0020] Erucic acid amide, stearic acid amide, and oleic acid amide all have excellent lubrication and anti-adhesion properties, which can significantly improve the efficiency of film blowing, make the surface finish of the finished film good, and effectively avoid the impact on the transparency of the product. Compared with oleic acid amide and stearic acid amide, erucic acid amide has better heat resistance and a larger molecular weight, and the migration speed of large molecular weight lubricants is slower. This avoids the accumulation of migratory lubricants on the surface of aluminum-plastic film, causing pollution.

[0021] Preferably, the polypropylene resin carrier is a combination of one or more of homopolypropylene, ethylene-propylene copolymer, butene-propylene copolymer, and octene-propylene copolymer.

[0022] Since the slip masterbatch needs to be mixed with the particles for preparing the polypropylene film, the polypropylene resin carrier needs to select a polymer similar to or the same as the composition of the polypropylene film. The above-mentioned different types of polypropylene resin carriers have a high melt index, high crystallinity, and good processing performance. When added as an additive masterbatch to the blown film formula, it will not affect the flexibility and mechanical strength of the polyolefin film and the aluminum-plastic film. At the same time, the addition of the above-mentioned polypropylene resin carriers has a better dispersion effect and does not affect the performance of the finished film.

[0023] Preferably, the nanoparticles are a combination of one or more of nano-titanium dioxide, nano-silicon dioxide and nano-zinc oxide.

[0024] As further preferred, the nanoparticles are nano-silicon dioxide.

[0025] Nanoparticles have an adsorption effect on migratory lubricants. Among them, adding nano silicon dioxide to the polypropylene resin carrier helps to improve the strength and elongation of the polypropylene resin carrier. At the same time, it is beneficial to improve the wear resistance of the polypropylene resin carrier, further improve the surface finish of the finished film, and enhance the anti-aging performance of the finished film. In addition, adding nano silicon dioxide helps to enhance its water absorption performance and improve the chemical resistance of the finished film. In addition, silicon dioxide itself can also be used as a lubricant and opening agent.

[0026] Preferably, the silane coupling agent is a combination of one or more of KH151, KH171, KH172, KH570, KH550, KH560, KH580, KH590, KH791, and KH792.

[0027] As a further preference, the silane coupling agent is a combination of one or more of KH151, KH171 and KH172.

[0028] As a further preference, the mass volume ratio of the nanoparticles added in the step (S.1) to the silane coupling agent is 1:2 to 1:5.

[0029] When the mass volume ratio of the added nanoparticles to the silane coupling agent is lower than 1:2, the degree of chemical grafting modification on the surface of the nanoparticles is insufficient, which can easily reduce its dispersibility in the slip masterbatch. When the mass volume ratio of the added nanoparticles to the silane coupling agent is higher than 1:5, the chemical grafting modification on the surface of the nanoparticles has been completed.

[0030] Preferably, the antioxidant is a combination of one or more of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) isooctyl acrylate, N-phenyl-α-naphthylamine, alkyl phenothiazine, benzotriazole, mercaptobenzothiazole, 2,6-di-tert-butyl-p-cresol, N-cyclohexyl-N'-phenyl-p-phenylenediamine, triphenyl phosphite, diphenyl-isooctyl phosphite, and tributyl phosphite.

[0031] As further preferred, the antioxidant is a combination of one or more of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylate, N-phenyl-α-naphthylamine, and alkyl phenothiazine.

[0032] 3-(3,5-di-tert-butyl-4-hydroxyphenyl) 2-ethylhexyl acrylate, N-phenyl-α-naphthylamine, and alkyl phenothiazine all have excellent antioxidant activity. Compared with N-phenyl-α-naphthylamine and alkyl phenothiazine, 3-(3,5-di-tert-butyl-4-hydroxyphenyl) 2-ethylhexyl acrylate has excellent antioxidant activity and also has lower volatility and excellent compatibility.

[0033] A method for preparing the nano-modified lubricant masterbatch as described above comprises the following steps:

[0034] (S.1) heating and activating the nanoparticles, then adding a silane coupling agent and mixing evenly, adding the mixed solution into anhydrous toluene for ultrasonic dispersion, and heating to reflux; after the reaction is completed, centrifuging, washing the precipitate with anhydrous ethanol, and drying to obtain modified nanoparticles;

[0035] (S.2) Calculate the weight of each component according to its weight and weigh each component, then disperse the components in a high-speed disperser and stir to mix them evenly, extrude and granulate them through a twin-screw extruder to obtain a nano-modified lubricating masterbatch.

[0036] As a further preference, a method for preparing the nano-modified lubricating masterbatch as described above specifically comprises the following steps: (S.1) Weigh 1 to 5 parts of nanoparticles and activate them at 300 to 500°C for 2 to 5 hours, then absorb 5 to 10 mL of silane coupling agent and disperse them together in 100 to 200 mL of toluene (water removed by 3A molecular sieve), ultrasonically disperse for 5 to 10 minutes, and heat to reflux. After the reaction is completed, let it stand and cool, and centrifuge it at a speed of 10,000 to 15,000 r / min. Wash the precipitate with anhydrous ethanol, and obtain modified nanoparticles after drying;

[0037] (S.2) Calculate the weight of each component according to its weight and weigh each component, then disperse the components in a high-speed disperser and stir to mix them evenly, extrude and granulate them through a twin-screw extruder to obtain a nano-modified lubricating masterbatch.

[0038] Preferably, the specific reaction conditions in step (S.2) are:

[0039] The weight is calculated according to the weight of each component and each component is weighed, and then each component is dispersed in a high-speed disperser and stirred and mixed evenly, and fully melt-blended through a twin-screw extruder, the melting temperature is 180-250°C, the screw speed is 60-100r / min, and the nano-modified smooth masterbatch is obtained by shearing and mixing the twin-screw extruder for 3-5 minutes, and then extruding, cooling, granulating, and drying.

[0040] The application of the nano-modified lubricating masterbatch as described above in the preparation of polyolefin film.

[0041] An aluminum-plastic film comprises a polyolefin film, characterized in that the polyolefin film is the polyolefin film described above.

[0042] Therefore, the present invention has the following beneficial effects:

[0043] (1) The migratory lubricant of the present invention has a slow migration speed, and a large amount of lubricant will not migrate outward to the surface of the aluminum-plastic film and accumulate in a short period of time, thereby effectively preventing the material from being contaminated;

[0044] (2) Compared with non-migrating lubricants, it has good compatibility with polyolefin resin matrix and is easier to disperse;

[0045] (3) In the preparation process of polyolefin films, a good smooth effect is achieved without affecting the subsequent processing performance, and the aluminum-plastic film is effectively prevented from being damaged during the deep punching process. DETAILED DESCRIPTION

[0046] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0047]

Preparation method of modified nanoparticles

[0048]

Modified Nano Silica A

[0049] Weigh 5 parts of nano-silica and activate them at 400℃ for 5h, then absorb 10mL KH151 and disperse them in 150mL toluene (dehydrated by 3A molecular sieve), ultrasonically disperse for 10min, and heat to reflux. After the reaction is completed, let it stand and cool, and centrifuge it at 13000r / min. Wash the precipitate with anhydrous ethanol, and obtain modified nano-silica A after drying.

[0050]

Modified Nano Silica B

[0051] Weigh 1 portion of nano-silica and activate it at 300℃ for 2h, then absorb 5mL KH151 and disperse them in 100mL toluene (water removed by 3A molecular sieve), ultrasonically disperse for 5min, and heat to reflux. After the reaction is completed, let it stand and cool, and centrifuge it at 10000r / min. Wash the precipitate with anhydrous ethanol, and obtain modified nano-silica B after drying.

[0052]

Modified Nano Silica C

[0053] Weigh 3 parts of nano-silica and activate them at 500℃ for 3.5h, then absorb 7.5mL KH151 and disperse them in 200mL toluene (water removed by 3A molecular sieve), ultrasonically disperse for 7.5min, and heat to reflux. After the reaction is completed, let it stand and cool, and centrifuge it at 15000r / min. Wash the precipitate with anhydrous ethanol, and obtain modified nano-silica C after drying.

[0054]

Modified Nano Titanium Dioxide D

[0055] Weigh 5 parts of nano titanium dioxide and activate them at 400℃ for 5h, then absorb 10mL KH151 and disperse them in 150mL toluene (water removed by 3A molecular sieve), ultrasonically disperse for 10min, and heat to reflux. After the reaction is completed, let it stand and cool, and centrifuge it at 13000r / min. Wash the precipitate with anhydrous ethanol, and obtain modified nano titanium dioxide D after drying.

[0056]

Modified Nano Zinc Oxide E

[0057] Weigh 5 parts of nano zinc oxide and activate them at 400℃ for 5h, then absorb 10mL KH151 and disperse them in 150mL toluene (water removed by 3A molecular sieve), ultrasonically disperse for 10min, and heat to reflux. After the reaction is completed, let it stand and cool, and centrifuge it at 13000r / min. Wash the precipitate with anhydrous ethanol, and dry it to obtain modified nano zinc oxide E.

[0058] Example 1

[0059] A method for preparing a nano-modified lubricating masterbatch, specifically comprising the following steps:

[0060] Weigh 80 parts of homopolymer polypropylene resin carrier, 10 parts of modified nano-silica A (prepared according to the preparation method of modified nanoparticles), 10 parts of erucic acid amide and 3 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) acrylate. Then disperse the components in a high-speed disperser and stir and mix them evenly, and fully melt and blend them through a twin-screw extruder, the melting temperature is 200°C, the screw speed is 80r / min, and the twin-screw extruder is sheared and mixed for 3 minutes, and then extruded, cooled, granulated, and dried to obtain a nano-modified smooth masterbatch.

[0061] Example 2

[0062] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from the embodiment 1 in that the number of parts of the homopolymerized polypropylene resin carrier weighed is 70 parts. The rest is the same as that in the embodiment 1.

[0063] Example 3

[0064] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from the embodiment 1 in that the number of parts of the homopolymerized polypropylene resin carrier weighed is 75 parts. The rest is the same as that in the embodiment 1.

[0065] Example 4

[0066] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from the embodiment 1 in that the number of parts of the homopolymerized polypropylene resin carrier weighed is 90 parts. The rest is the same as that in the embodiment 1.

[0067] Example 5

[0068] This embodiment provides a method for preparing a nano-modified lubricating masterbatch, which differs from the embodiment 1 in that the weight of the modified nano-silicon dioxide is 5 parts. The rest is the same as that in the embodiment 1.

[0069] Example 6

[0070] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from the embodiment 1 in that the weight of the modified nano-silicon dioxide is 8 parts. The rest is the same as that in the embodiment 1.

[0071] Example 7

[0072] This embodiment provides a method for preparing a nano-modified lubricating masterbatch, which differs from the embodiment 1 in that the weight of the modified nano-silicon dioxide is 15 parts. The rest is the same as that in the embodiment 1.

[0073] Example 8

[0074] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from Embodiment 1 in that the number of parts of erucamide weighed is 5 parts, and the rest is the same as that in Embodiment 1.

[0075] Example 9

[0076] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from the embodiment 1 in that the number of parts of erucamide weighed is 12 parts, and the rest is the same as that in the embodiment 1.

[0077] Example 10

[0078] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from the embodiment 1 in that the number of parts of erucamide weighed is 15 parts. The rest is the same as that in the embodiment 1.

[0079] Embodiment 11

[0080] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from Embodiment 1 in that: the portion of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylate is 1 portion. The rest is the same as in Embodiment 1.

[0081] Example 12

[0082] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from Embodiment 1 in that: the number of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylate is 5 parts. The rest is the same as in Embodiment 1.

[0083] Embodiment 13

[0084] A method for preparing a nano-modified lubricating masterbatch, specifically comprising the following steps:

[0085] Weigh 80 parts of homopolymer polypropylene resin carrier, 10 parts of modified nano-silica B (prepared according to the preparation method of modified nanoparticles), 10 parts of erucic acid amide and 3 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) acrylate. Then disperse the components in a high-speed disperser and stir and mix them evenly, and fully melt and blend them through a twin-screw extruder, with a melting temperature of 180°C and a screw speed of 60r / min. Shear and mix them through a twin-screw extruder for 5 minutes, then extrude, cool, granulate and dry to obtain a nano-modified smooth masterbatch.

[0086] Embodiment 14

[0087] A method for preparing a nano-modified lubricating masterbatch, specifically comprising the following steps:

[0088] Weigh 80 parts of homopolymer polypropylene resin carrier, 10 parts of modified nano-silica C (prepared according to the preparation method of modified nanoparticles), 10 parts of erucic acid amide and 3 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) acrylate. Then disperse the components in a high-speed disperser and stir and mix them evenly, and fully melt and blend them through a twin-screw extruder. The melting temperature is 250°C and the screw speed is 100r / min. Shear and mix them in the twin-screw extruder for 4 minutes, then extrude, cool, granulate and dry to obtain a nano-modified smooth masterbatch.

[0089] Comparative Example 1

[0090] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from the embodiment 1 in that the modified nano-silicon dioxide is weighed in 1 part. The rest is the same as that in the embodiment 1.

[0091] Comparative Example 2

[0092] This embodiment provides a method for preparing a nano-modified lubricating masterbatch, which differs from the embodiment 1 in that the weight of the modified nano-silicon dioxide is 20 parts. The rest is the same as that in the embodiment 1.

[0093] Comparative Example 3

[0094] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from Embodiment 1 in that: the portion of erucamide weighed is 1 portion. The rest is the same as in Embodiment 1.

[0095] Comparative Example 4

[0096] This embodiment provides a method for preparing a nano-modified slippery masterbatch, which differs from the embodiment 1 in that the number of parts of erucamide weighed is 20 parts, and the rest is the same as that in the embodiment 1.

[0097] Comparative Example 5

[0098] This embodiment provides a method for preparing a lubricating masterbatch, which differs from the embodiment 1 in that the unmodified nano-silicon dioxide is weighed in 10 parts. The rest is the same as that in the embodiment 1.

[0099] Comparative Example 6

[0100] This embodiment provides a method for preparing a lubricating masterbatch, which differs from the embodiment 1 in that the polypropylene resin carrier weighed is 80 parts of ethylene-propylene copolymer. The rest is the same as that in the embodiment 1.

[0101] Comparative Example 7

[0102] This embodiment provides a method for preparing a lubricating masterbatch, which differs from the embodiment 1 in that the polypropylene resin carrier weighed is 80 parts of a copolymer of butene and propylene. The rest is the same as that in the embodiment 1.

[0103] Comparative Example 8

[0104] This embodiment provides a method for preparing a lubricating masterbatch, which differs from the embodiment 1 in that the migratory lubricant weighed is 10 parts of stearic acid amide. The rest is the same as that in the embodiment 1.

[0105] Comparative Example 9

[0106] This embodiment provides a method for preparing a lubricating masterbatch, which is different from the embodiment 1 in that the migratory lubricant weighed is 10 parts of oleamide. The rest is the same as that in the embodiment 1.

[0107] Comparative Example 10

[0108] This embodiment provides a method for preparing a lubricating masterbatch, which differs from the embodiment 1 in that the antioxidant weighed is 3 parts of N-phenyl-α-naphthylamine. The rest is the same as that in the embodiment 1.

[0109] Comparative Example 11

[0110] This embodiment provides a method for preparing a lubricating masterbatch, which differs from the embodiment 1 in that the antioxidant weighed is 3 parts of alkyl phenothiazine. The rest is the same as that in the embodiment 1.

[0111] Comparative Example 12

[0112] This example provides a method for preparing a lubricating masterbatch, which differs from Example 1 in that 10 portions of modified nano titanium dioxide D (prepared according to the above-mentioned method for preparing modified nanoparticles) are weighed. Others are the same as in Example 1.

[0113] Comparative Example 13

[0114] This embodiment provides a method for preparing a lubricating masterbatch, which differs from the embodiment 1 in that 10 parts of modified nano zinc oxide E (prepared according to the preparation method of the modified nano particles) are weighed. The rest is the same as that in the embodiment 1.

[0115] The specific composition ratios of the nano-modified lubricating masterbatch prepared according to the preparation methods in Examples 1 to 14 and Comparative Examples 1 to 13 are shown in Table 1 below.

[0116] Table 1

[0117]

[0118]

[0119]

Preparation method of polypropylene film

[0120] The polypropylene film is composed of three layers from the inside to the outside, namely, a heat sealing layer, a core layer, and a corona layer. The heat sealing layer contains 20 to 60 parts of polyolefin elastomer, 10 to 80 parts of random copolymer polypropylene resin, and 1 to 10 parts of nano-modified slip masterbatch. The core layer contains 10 to 50 parts of olefin elastomer, 10 to 90 parts of block copolymer polypropylene resin, and 1 to 10 parts of nano-modified slip masterbatch. The corona layer contains 1 to 90 parts of acid-modified polyolefin resin and 10 to 30 parts of random copolymer polyolefin elastomer. Among them, the nano-modified slip masterbatch is prepared according to the preparation methods in Examples 1 to 14 and Comparative Examples 1 to 13. The particles mixed in proportion in the above layers are added to the first, second, and third screws of the co-extrusion equipment, respectively, and the extrusion temperature is set to 180 to 300°C. The resin flowing out of the extruder is cast through a T-die with a die temperature of 200-300°C. After casting, it is cooled to form a film, trimmed and rolled up to make a polypropylene film.

[0121]

Performance test and analysis of nano-modified slippery masterbatch

[0122] The nano-modified lubricating masterbatch prepared by the preparation methods in Examples 1 to 14 and Comparative Examples 1 to 13 was added to the core layer according to the normal production ratio of polypropylene film, and melt-blended by a twin-screw extruder. Then cooled and granulated to obtain lubricating agent-core layer particles, and then a polypropylene film was obtained by three-layer co-extrusion. In order to verify the lubricating effect and stability of the nano-modified lubricating masterbatch, the following tests were performed on the prepared polypropylene film:

[0123] The polypropylene film was placed at room temperature, and the mass of the lubricant precipitated on the inner surface of the polypropylene film was measured after 1 day, 3 days, 5 days, 7 days, 15 days, 20 days, 25 days, and 30 days. The results are shown in Table 2. The mass of the lubricant was tested using liquid chromatography, and the unit is mg / m 2 .

[0124] Table 2

[0125] project 1 day 3 days 5 days 7 days 15 days 20 days 25 days 30 days Example 1 0.4 1.2 3.1 5.2 7.8 9.4 10 10 Example 2 0.5 1.6 3.5 5.8 8.4 10 10.6 11 Example 3 0.3 1.1 3.0 5.2 7.2 7.8 9.2 9.5 Example 4 0.3 1.0 3.0 5.1 6.9 7.4 8.7 9 Example 5 0.5 1.5 3.2 5.6 8.4 10 12.4 14 Example 6 0.5 1.2 3.0 5.0 7.0 8.1 9.4 11.8 Example 7 0.5 1.1 2.8 4.8 6.2 6.9 7.0 6.9 Example 8 0.5 1.2 2.6 4.9 6.2 7.1 6.9 7.0 Example 9 0.5 1.6 3.3 5.6 7.8 9.4 10.2 12.1 Example 10 0.6 2.1 4.0 6.1 8.9 11.4 13.8 15 Embodiment 11 0.4 1.3 3.2 5.3 7.9 9.3 10 10 Example 12 0.4 1.2 3.1 5.2 7.8 9.4 9.9 10.1 Embodiment 13 0.5 1.5 3.2 5.6 8.4 10 12.4 14 Embodiment 14 0.5 1.2 3.0 5.0 7.0 8.1 9.4 11.8 Comparative Example 1 1 2.4 4.7 6.6 9.5 11.8 15 16.1 Comparative Example 2 0.4 1.0 3.1 5.3 6.1 6.4 6.6 6.6 Comparative Example 3 0.1 0.4 1.8 3.2 4.1 4.8 4.9 5 Comparative Example 4 2.2 4.8 7.6 10.8 13.7 16.4 18.1 20 Comparative Example 5 2.5 5.3 8.0 11.3 14.4 17.1 19 20.6 Comparative Example 6 0.4 1.2 3.1 5.3 7.8 9.3 10.1 10.1 Comparative Example 7 0.4 1.2 3.0 5.1 7.7 9.5 10 10.1 Comparative Example 8 0.5 1.6 3.5 5.8 8.4 10 10.6 11 Comparative Example 9 0.5 1.2 3.0 5..8 8.2 10.3 10.7 11.3 Comparative Example 10 0.4 1.2 3.1 5.3 7.8 9.2 10 9.9 Comparative Example 11 0.4 1.2 3.1 5.2 7.8 9.3 10 10 Comparative Example 12 0.4 1.2 3.1 5.1 7.8 9.4 10.1 10.1 Comparative Example 13 0.4 1.2 3.1 5.1 7.7 9.3 9.9 10 .

[0126] From the data analysis in Tables 1 to 2, it can be seen that when the amount of modified nano-silica added is small (Example 4, Comparative Example 1), its ability to adsorb the lubricant (erucic acid amide) is reduced, the speed of precipitating the lubricant increases, and the final precipitation amount will also increase. When unmodified nano-silica is added (Comparative Example 5), its adsorption performance is extremely low, the lubricant precipitation speed is the fastest, and the final precipitation amount is also the largest. When the amount of lubricant (erucic acid amide) added is large (Example 7, Comparative Example 4), it exceeds the adsorption capacity of the modified nano-silica, which increases the precipitation speed of the lubricant and the final precipitation amount. The content of the lubricant in Example 1 does not change much during the 20-30 days of the lubricant, and it can basically be considered to be in a stable state. As time goes on, no lubricant will continue to precipitate. The precipitation amount of 10g ensures that the aluminum-plastic film has a certain degree of smoothness and will not be easily damaged during deep punching (the less precipitation, the easier it is to break. Generally, if the precipitation amount is less than 6.0g, the breakage rate of the aluminum-plastic film will be extremely high). At the same time, too much lubricant will not precipitate, causing excessive adhesion of lubricant to the mold surface during deep punching, affecting work efficiency and causing product contamination (the more precipitation, the easier it is to cause problems. Generally, problems will be very serious if it exceeds 16g). Comprehensively considered, in order to avoid contaminating the deep punching mold, the surface content of the lubricant should not be higher than 16mg / m 2 In order to ensure smooth performance, it should not be less than 6mg / m 2 Therefore, the surface content of the lubricant is 10 mg / m 2 By comparing Example 1 with Comparative Examples 8 and 9, erucic acid amide has a slower migration speed, which is mainly related to its larger molecular weight. The types of polypropylene resin carrier, modified nanoparticles and antioxidants have little effect on the migration of the lubricant.

[0127] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.

Claims

1. A nano-modified lubricating masterbatch, characterized in that: Includes the following components: 5-15 parts of modified nanoparticles, 5-15 parts of migratory lubricant, 70-90 parts of polypropylene resin carrier and 1-5 parts of antioxidant; The outer surface of the modified nanoparticles is chemically grafted with a silane coupling agent; the migratory lubricant is a combination of one or more of stearic acid amide, N,N-ethylene distearic acid, erucic acid amide, oleic acid amide, and stearyl n-butyl ester; The preparation method of the nano-modified smooth masterbatch comprises the following steps: (S.1) heating and activating the nanoparticles, then adding a silane coupling agent and mixing evenly, adding the mixed solution into anhydrous toluene for ultrasonic dispersion, and heating to reflux; after the reaction is completed, centrifuging, washing the precipitate with anhydrous ethanol, and drying to obtain modified nanoparticles; the nanoparticles are a combination of one or more of nano-titanium dioxide, nano-silicon dioxide, and nano-zinc oxide; (S.2) Calculate the weight of each component according to its weight and weigh each component, then disperse the components in a high-speed disperser and stir and mix them evenly, extrude and granulate them through a twin-screw extruder to obtain a nano-modified lubricating masterbatch.

2. The nano-modified lubricating masterbatch according to claim 1, characterized in that: The polypropylene resin carrier is a combination of one or more of homopolypropylene, ethylene-propylene copolymer, butene-propylene copolymer, and octene-propylene copolymer.

3. The nano-modified lubricating masterbatch according to claim 1, characterized in that: The silane coupling agent is a combination of one or more of KH151, KH171, KH172, KH570, KH550, KH560, KH580, KH590, KH791, and KH792.

4. The nano-modified lubricating masterbatch according to claim 1, characterized in that: The specific reaction conditions in the step (S.2) are: The weight is calculated according to the weight of each component and each component is weighed, and then each component is dispersed in a high-speed disperser and stirred and mixed evenly, and fully melt-blended through a twin-screw extruder, the melting temperature is 180-250°C, the screw speed is 60-100r / min, and the nano-modified smooth masterbatch is obtained by shearing and mixing the twin-screw extruder for 3-5 minutes, and then extruding, cooling, granulating, and drying.

5. Use of the nano-modified lubricating masterbatch as claimed in any one of claims 1 to 4 in the preparation of polyolefin films.

6. An aluminum-plastic film comprising a polyolefin film, characterized in that: The polyolefin film is the polyolefin film according to claim 5.

Citation Information

Patent Citations

  • Silicone opening slipping agent master batch composition for plastic film and preparation method of silicone opening slipping agent master batch

    CN109705443A

  • Slipping coating liquid, aluminum-plastic film and lithium ion battery

    CN110041817A

  • Polyethylene anti-blocking smooth master batch and preparation method thereof

    CN103849033A

  • BOPP film with endurable and smoothness characteristics and preparation method therefor

    CN105172284A

  • Preparation method of polypropylene melt-blown non-woven fabric electret master batch material with high filterability

    CN112480542A